2019
DOI: 10.3747/co.26.4749
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Radionecrosis in Single-Fraction Radiosurgery Compared with Fractionated Radiotherapy in the Treatment of Brain Metastasis

Abstract: Introduction Radiation-induced brain necrosis [“radionecrosis” (rn)] is a relatively uncommon but potentially severe adverse effect of stereotactic radiosurgery (srs) for brain metastasis. Although dose, volume, and hypofractionation have been suggested to affect rn rates, patient and treatment variability in this population make it difficult to clearly delineate the risk. We set out to establish the effect of fractionation on rn rates by reviewing patients receiving simultaneous multi-fraction and single-frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…In addition, similarly to the work of Minniti et al radiation necrosis was also markedly reduced in the FSRT arm with a radionecrosis rate of 0% in the FSRT arm compared to 39.8% for the SRS group ( 31 ). In the subgroup of large brain metastases, some negative comparative studies have also been published, which were mainly characterized by small patient numbers ( 32 34 ). However, we are unaware of any comparative investigations of FSRT and SRS that demonstrated significantly inferior results for the FSRT group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similarly to the work of Minniti et al radiation necrosis was also markedly reduced in the FSRT arm with a radionecrosis rate of 0% in the FSRT arm compared to 39.8% for the SRS group ( 31 ). In the subgroup of large brain metastases, some negative comparative studies have also been published, which were mainly characterized by small patient numbers ( 32 34 ). However, we are unaware of any comparative investigations of FSRT and SRS that demonstrated significantly inferior results for the FSRT group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies seem to support the latter proposal. [9,10,17] As illustrated in this report, progressive extracranial disease remains a major problem for many patients with brain metastatic disease. Promising therapeutic breakthroughs Table 3: Tumor volume dynamics of Met 2 and Met 3 throughout treatment (GKRS1-GKRS3) and during follow-up.…”
Section: Further Aspectsmentioning
confidence: 83%
“…Other than single-fraction SRS, staged-treatment and fractionated irradiation are also available to reduce the risk of perifocal radiation necrosis [6,7,[11][12][13][15][16][17][18]26]. Fractionated doses help to spare normal tissues by allowing time for the repair of sublethal damage and/or potential lethal damage and enhance tumor cell killing by allowing reoxygenation between doses [27].…”
Section: Discussionmentioning
confidence: 99%
“…Under in vivo conditions with blood flow, reoxygenation is expected to enhance the effectiveness of irradiation to the target tumor [28]. The optimal dose fractionation for a large brain metastasis not responsive to single-fraction SRS has not been established well [15]. Inoue et al reported the importance of a 14 Gy equivalent dose-volume in five-fraction CyberKnife SRS for large brain metastases [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation